Unravelling the mechanisms of a protein refolding process based on the association of detergents and co‐solvents. (19th May 2016) - Michaux, C.; Roussel, G.; Lopes‐Rodrigues, M.; Matagne, A.; Perpète, E.A.
Abstract : A new technique associating the detergent Sodium Dodecyl Sulphate (SDS) and an alcohol‐type co‐solvent has been set up, showing an unexpected efficiency to refold several types of soluble or membrane proteins. The present contribution deepens the fundamental knowledge on the phenomena underlying this process, considering the refolding of two model peptides featuring the main protein secondary structures: α‐helix and β‐sheet. Their refolding was monitored by fluorescence and circular dichroism, and it turns out that: (i) 100% recovery of the folded structure is observed for both peptides, (ii) the highest the SDS concentration, the more co‐solvent to be added to recover the peptides' native structures, (iii) a high alcohol concentration is required to alter the SDS denaturing properties, (iv) the co‐solvent performance relies on its specific lipophilic–hydrophilic balanced character, (v) the size of the micelle formed by the detergent does not enter the process critical parameters, and (vi) increasing the salt concentration up to 1 M NaCl has a beneficial impact on the process efficiency. These mechanistic aspects will help us to improve the method and extend its application. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd. Abstract : The contribution deepens the knowledge on phenomena underlying a protein refolding method based on the association of Sodium Dodecyl Sulphate (SDS) and an alcohol‐type co‐solvent. Following the two model peptide's refolding, it turns out that the co‐solvent performance relies on its specific lipophilic–hydrophilic character. The co‐solvent reduces the SDS–peptide interactions, allowing their renaturation. The micelle size seems not an essential key and adding salt has a beneficial effect. These mechanistic aspects will help improving the method and extending its application.